Analisis Tikungan Rawan Kecelakaan Jalan Jatinegara-Slawi - Jati Nugroho; Suprapto Hadi; Bramantyo Adji Waskito; Novia Maharani; Arsy Maretta Ella S (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
This study investigates the geometric conditions of a horizontal curve on the Jatinegara-Slawi intercity road segment, an area prone to traffic accidents due to poor visibility and inadequate design standards. Field surveys and geometric measurements were conducted using terrestrial methods, supported by digital mapping with AutoCAD. Analysis followed the Bina Marga design guidelines to evaluate curve conformity, Stopping Sight Distance (SSD) and Overtaking Sight Distance (OSD) are important measurements in designing roads and ensuring safety. The results indicate that the existing curve geometry does not satisfy Full-Circle design criteria due to excessive superelevation, leading to the application of a Spiral–Spiral curve type. The calculated design includes a 30 m curve radius, 47 m spiral length, 45° spiral angle, 94 m total curve length, SSD of 27 m, and OSD of 155.6 m, with a recommended 3 m lateral clearance. To improve road safety, the installation of one convex mirror and 16 reflective guideposts is proposed. This study underscores the significance of geometric principles adjustments and the addition of safety features to enhance visibility and reduce the risk of accidents, especially in routes with high traffic and complex terrain